Culturally Relevant Teacher Education: A Canadian Inner-City Case - Hesch, Rick (Canadian Journal of Education/Revue canadienne de l’éducation, 1999)
This case study of an inner-city teacher education program documents the tensions at work on a social reconstructionist academic staff attempting to produce a culturally relevant teacher education program. Cultural relevance here includes three features: supporting academic achievement, maintaining cultural competence, and developing critical consciousness. All interests converge on the need to produce academically and technically competent teachers. Beyond this, the staff remain mindful of the dominant social and educational context within which they work and at the same time attempt to meet the longer-term interests of their students and culturally different inner-city communities. The possibilities for success have lessened in the political economy of the 1990s, but the study provides concrete instances of developing a culturally relevant teacher education program. Cette étude de cas portant sur un programme de formation à l’enseignement dans des écoles de quartiers défavorisés décrit les tensions au sein du personnel enseignant cher- chant à produire un programme de formation des maîtres culturellement significatif. Trois éléments définissent la pertinence culturelle d’un programme : il doit promouvoir la réussite scolaire, être adapté à la culture et développer une pensée critique. Tous les intervenants s’accordent sur la nécessité de produire des enseignants compétents. Cela dit, le personnel doit garder à l’esprit le contexte éducatif et social dominant dans lequel il travaille tout en essayant de tenir compte des intérêts à long terme des élèves et de diverses communautés culturelles implantées dans des quartiers défavorisés. L’étude fournit des exemples concrets de la marche à suivre pour élaborer un programme de formation à l’enseignement culturellement significatif.